The Evolution of Hadith Studies: From Early Writing to Digital Verification in the Era of Modern Science - Himmah Makhollah Arofina; Hanafi Nugraha (KEDJATI Journal of Islamic Civilization, 2026)
The rapid expansion of digital access to information has transformed hadith studies, creating a critical challenge in the widespread dissemination of fabricated traditions and the limited availability of reliable digital verification systems. This study aims to examine the evolution of hadith verification from classical scholarship to contemporary digital approaches and to evaluate their effectiveness in preserving authenticity. A qualitative approach was employed through a literature review and historical comparative analysis to trace the development of hadith criticism, from traditional sanad and matan evaluation to emerging technologies such as artificial intelligence and blockchain. The findings indicate that although digital platforms enhance accessibility and accelerate dissemination, current verification tools remain insufficient for comprehensive and accurate authentication. Consequently, classical methodologies continue to serve an indispensable role in maintaining scholarly rigor. Besides, this study argues for an integrative framework combining traditional hadith criticism with advanced technological innovations to address current challenges. Hence, it concludes that such synergy provides a more reliable pathway for safeguarding hadith authenticity and offers a conceptual foundation for developing robust digital verification systems capable of mitigating contemporary disinformation.